l is for llama - Gosling , Livi; Appleton , Polly; Beets, Sally (London Dorling Kindersley Limited, 2021)
The latest title in DK's new alphabet series--L is for Llama looks at llama-related words that begin with the letter "l." Take a first look at the lovely lives of llamas in this beautifully illustrated ebook for babies
Keywords: English language Alphabet; Vocabulary